Efisiensi Proses Penyediaan Material di PT.X - Darwin Santoso; Tanti Octavia (Jurnal Titra, 2019)
PT. X is engaged in cigarette manufacturing and is one of the leading tobacco companies in Indonesia and even the world. Planning to supply materials is a very important part of the production process. This research focuses on efficiency that can be done to simplify and accelerate the process of conducting various material supply planning activities. The two activities that will be discussed are PR review and material readiness. The efficiency process carried out is by making a proposal template that will facilitate the user in carrying out his activities. PR review templates that have been made are able to shorten the required activity time by 69.68%. While the material readiness template that was made was able to shorten the time of activities by 81.13%.